The Combined Effects of Co-Culture and Substrate Mechanics on 3D Tumor Spheroid Formation within Microgels Prepared via Flow-Focusing Microfluidic Fabrication - Dongjin Lee; Chaenyung Cha (MDPI AG, 2018)
Tumor spheroids are considered a valuable three dimensional (3D) tissue model to study various aspects of tumor physiology for biomedical applications such as tissue engineering and drug screening as well as basic scientific endeavors, as several cell types can efficiently form spheroids by themselves in both suspension and adherent cell cultures. However, it is more desirable to utilize a 3D scaffold with tunable properties to create more physiologically relevant tumor spheroids as well as optimize their formation. In this study, bioactive spherical microgels supporting 3D cell culture are fabricated by a flow-focusing microfluidic device. Uniform-sized aqueous droplets of gel precursor solution dispersed with cells generated by the microfluidic device are photocrosslinked to fabricate cell-laden microgels. Their mechanical properties are controlled by the concentration of gel-forming polymer. Using breast adenocarcinoma cells, MCF-7, the effect of mechanical properties of microgels on their proliferation and the eventual spheroid formation was explored. Furthermore, the tumor cells are co-cultured with macrophages of fibroblasts, which are known to play a prominent role in tumor physiology, within the microgels to explore their role in spheroid formation. Taken together, the results from this study provide the design strategy for creating tumor spheroids utilizing mechanically-tunable microgels as 3D cell culture platform.